The Relationship between Ideological and Political Education and Students’ Social Responsibility - Huang, Jie (Education as Change, 2025)
The purpose of this study is to identify the relationship between ideological and political education and students’ social responsibility. Methodologically, the study involves 76 first-year Chinese undergraduate students who received ideological and political education. The study offers a theoretical substantiation of the features of students’ formation of social responsibility in the process of ideological and political education. This allows for an expansion of the understanding of the formation of an individual’s “I” in the process of socialisation. The practical significance of the research results is derived from their potential application to enhance the effectiveness of ideological and political education and to develop students’ social responsibility in the context of the digitalisation of the educational process, considering both personal and institutional factors within the Chinese educational system. In addition, the obtained research results can be used to harmonise the “I” concept of the individual in its interaction with the social environment. The implications underscore the correlation between students’ ideological and political education and their social responsibility and highlight the importance of ideological and political education in fostering personal social responsibility development and forming socially responsible attitudes towards academic pursuits and future professional activities.